Lack of evidence supporting a role of IFN-β and TGF-β in differential polarization of Bordetella pertussis specific-T cell responses. (January 2021) - da Silva Antunes, Ricardo; Quiambao, Lorenzo G.; Soldevila, Ferran; Sutherland, Aaron; Peters, Bjoern; Sette, Alessandro
Highlights: Pertussis resurgence is associated with waning of vaccine-induced immunity. Type of childhood pertussis vaccine defines long-term T cell polarization. IFN-β increases cytokine responses to pertussis stimulated naïve CD4 + T cells. TGF-β increases proliferation of pertussis stimulated naïve CD4 + T cells. Lack of evidence on the role of long-lasting T cell polarization by IFN-β or TGF-β. Abstract: Bordetella Pertussis (BP) vaccine-induced immunity is waning worldwide despite excellent vaccine coverage. Replacement of the whole-cell inactivated vaccine (wP) by an acellular subunit vaccine (aP) is thought to play a major role and to be associated with the recurrence of whooping cough. Previously, we detected that the polarization towards a Th2 and Th1/Th17 response in aP and wP vaccinees, respectively, persists upon aP boosting in adolescents and adults. Additionally, IL-9 and TGF-β were found to be up-regulated in aP-primed donors and network analysis further identified IFN-β as a potential upstream regulator of IL-17 and IL-9. Based on these findings, we hypothesized that IFN-β produced following aP vaccination may lead to increased IL-9 and decreased IL-17 production. Also, due to the well characterized role of TGF-β in both Th17 and Th9 differentiation, we put forth that TGF-β addition to BP-stimulated CD4 + T cells might modulate IL-17 and IL-9 production. To test this hypothesis, we stimulated in vitro cultures of PBMC or isolated naive CD4 + T cells from aP vs wP donors with a pool of BP epitopes and assessed the effect of IFN-β or TGF-β in proliferative responses as well as in the cytokine secretion of IL-4, IL-9, IL-17, and IFN-γ. IFN-β reduced BP-specific proliferation in PBMC as well as cytokine production but increased IL-9, IL-4, and IFN-γ cytokines in naïve CD4 + T cells. These effects were independent of the childhood vaccination received by the donors. Similarly, TGF-β reduced BP-specific proliferation in PBMC but induced proliferation in naïve CD4 + T cells. However, stimulation was associated with a generalized inhibition of cytokine production regardless of the original aP or wP vaccination received by the donors. Our study suggests that key T cell functions such as cytokine secretion are under the control of antigen stimulation and environmental cues but molecular pathways different than the ones investigated here might underlie the long-lasting differential cytokine production associated with aP- vs wP-priming in childhood vaccination.